2017
DOI: 10.3389/fpsyt.2017.00225
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Transcription of NRG-ErbB Pathway Genes Are Upregulated in Treatment-Resistant Schizophrenia

Abstract: Investigation of peripheral gene expression patterns of transcripts within the NRG–ErbB signaling pathway, other than neuregulin-1 (NRG1), among patients with schizophrenia and more specifically treatment-resistant schizophrenia (TRS) is limited. The present study built on our previous work demonstrating elevated levels of NRG1 EGFα, EGFβ, and type I(Ig2) containing transcripts in TRS by investigating 11 NRG–ErbB signaling pathway mRNA transcripts (NRG2, ErbB1, ErbB2, ErbB3, ErbB4, PIK3CD, PIK3R3, AKT1, mTOR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Compared to the healthy control group, serum EGF was significantly lower in patients prior to drug or combined drug + ECT treatment, in agreement with several previous reports of lower serum EGF in both acute and chronic schizophrenia patients (21,24). EGF regulates cell growth, proliferation, and differentiation through binding to high-affinity EGFRs (1,4,9). Accumulating evidence suggests that neurotrophic factors and cytokines mutually interact to influence neurogenesis and transmitter release, both of which are disrupted in schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to the healthy control group, serum EGF was significantly lower in patients prior to drug or combined drug + ECT treatment, in agreement with several previous reports of lower serum EGF in both acute and chronic schizophrenia patients (21,24). EGF regulates cell growth, proliferation, and differentiation through binding to high-affinity EGFRs (1,4,9). Accumulating evidence suggests that neurotrophic factors and cytokines mutually interact to influence neurogenesis and transmitter release, both of which are disrupted in schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
“…The cytokine epidermal growth factor (EGF) has been proposed as an important effector molecule in schizophrenia (1)(2)(3). Dysregulation of dopaminergic signaling is implicated in the expression of schizophrenic symptoms, and it is well documented that EGF signaling regulates dopaminergic neuron activity and monoamine metabolism in the brain (2,(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…NRG1 methylation rates did not show any significant group differences although earlier studies revealed higher expression levels of NRG1 in treatment-resistant schizophrenia [48] and clozapine-treated schizophrenic patients [49]. Therefore, it might be concluded that higher expression of NRG1 is not regulated via the alteration of methylation rates.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, Haring et al 20 reported that serum levels of EGF were increased in FEP patients, but after for approximately 7 months antipsychotic medication treatment, EGF levels decrease and are related to the clinical improvement of FEP patients. It is well known that EGF protects dopaminergic neurons from glutamate toxicity in culture 6,16,29,30 . Serum EGF levels in patients were lower or higher than in the control group during all the stages of the illness, suggesting that dopaminergic neurons, in the case of patients, were obviously abnormal, and this abnormality is implicated in the mental symptoms and pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%